2018
DOI: 10.4103/1673-5374.239434
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced neurotoxicity: still much ado

Abstract: Cadmium (Cd) is a highly toxic heavy metal that accumulates in living system and as such is currently one of the most important occupational and environmental pollutants. Cd reaches into the environment by anthropogenic mobilization and it is absorbed from tobacco consumption or ingestion of contaminated substances. Its extremely long biological half-life (approximately 20–30 years in humans) and low rate of excretion from the body cause cadmium storage predominantly in soft tissues (primarily, liver and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(71 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Cd pollution in animal production has been a problem for several countries, and in some situations, the concentration of Cd in manure and animal feed can reach up to even 130 mg/kg ( Li et al., 2010 ). Chronic exposure to Cd can induce hepatotoxicity, renal dysfunction, and neurotoxicity ( Branca et al., 2018 , Rong et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cd pollution in animal production has been a problem for several countries, and in some situations, the concentration of Cd in manure and animal feed can reach up to even 130 mg/kg ( Li et al., 2010 ). Chronic exposure to Cd can induce hepatotoxicity, renal dysfunction, and neurotoxicity ( Branca et al., 2018 , Rong et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to Cd also severely affects the function of the nervous system [8,9,10,11], with symptoms including headache and vertigo, olfactory and motor dysfunction, peripheral neuropathy, decreased equilibrium and ability to concentrate, and learning disabilities [12,13,14,15]. Although studies on the central nervous system (CNS) Cd distribution demonstrated that this metal could not easily get into the brain due to the presence of the blood brain barrier (BBB) [16,17], a Cd-induced BBB dysfunction and permeability increase has been demonstrated in in vivo models [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that environmental toxicant-induced elevation of ROS in the brain may contribute to cognitive dysfunction [ 56 , 57 ]. Both obesity and cadmium exposure are associated with increased levels of ROS and several human diseases [ [58] , [59] , [60] ].…”
Section: Discussionmentioning
confidence: 99%